Radio frequency identification: Evolution of transponder circuit design - Mohd, Yasin, F; Khaw, M. K; Reaz, M. B. I. (2006)
A basic RFID system consists of three components: an antenna, a reader and a transponder, commonly called a tag. Tag designs are the most well researched over the years and different designs came about to suit their application in various fields. This article focuses on approaches, improvements and comparison Of various transponder circuits. It is observed that the trend is toward the design of passive tags, as opposed to active tags. This article opens a way for researchers to obtain, a good understanding of RFID transponder circuit design, which will help them to develop more powerful, flexible and efficient applications.